If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -3(2m + -4) = 9 Reorder the terms: 15 + -3(-4 + 2m) = 9 15 + (-4 * -3 + 2m * -3) = 9 15 + (12 + -6m) = 9 Combine like terms: 15 + 12 = 27 27 + -6m = 9 Solving 27 + -6m = 9 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + -6m = 9 + -27 Combine like terms: 27 + -27 = 0 0 + -6m = 9 + -27 -6m = 9 + -27 Combine like terms: 9 + -27 = -18 -6m = -18 Divide each side by '-6'. m = 3 Simplifying m = 3
| 5n-12=2(-n+1) | | 5n^3-31n^2+30n=0 | | 66.64+7.42+8.6=y | | 0.2x^2+3.7x-1.9=0 | | h=-16t^2+80t+44 | | 7(5x+3)=35x+21 | | -18(2)-6y=-33 | | 5(n+6)(n-1)=0 | | 4.67x-1.5=1.25 | | x+-4.3=23 | | (2x-5)(4x^2+10x+25)= | | 6y-.75=3.25+2y | | (4x+y)(6x-7y)= | | 4t(2t-10)=0 | | Ln(x+8)-ln(x)=1 | | -43+x=23 | | -1+5p=2(2p-3) | | -105-x=6x+105 | | 45=71-y | | 162-16t^2=0 | | 10x^2+20x+30=180 | | 6x=22x^2+11x+1 | | 45=73-y | | 45=65-y | | -k+2=-k-2(3+k) | | 2.625+4m=m+3.25 | | -6x-29=5x+7 | | -2C+8=24 | | 5x^8+30x^6-35x^4=0 | | -97-8x=10x+137 | | 45=80-y | | 3(x+2.93)=2x |